2015
DOI: 10.1016/j.jad.2014.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Future disposition and suicidal ideation: Mediation by depressive symptom clusters

Abstract: Background In line with hopelessness theory, both increased negative expectancies and reduced positive expectancies for the future have been associated with suicidal ideation. This study evaluated two depression symptom clusters as mediators of the relationship between future disposition and suicide: subjective feelings of depression and self-blame. Methods Data from 140 undergraduate students with moderate to severe depression symptoms are presented who completed the Beck Scale for Suicidal Ideation, Beck D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
5
20
0
1
Order By: Relevance
“…Previous study has shown the mediating effect of some depressive symptom clusters such as self-blame on the relationship between hopelessness with SI in undergraduate students (Ballard et al, 2015). The current findings also found this effect in clinical sample.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous study has shown the mediating effect of some depressive symptom clusters such as self-blame on the relationship between hopelessness with SI in undergraduate students (Ballard et al, 2015). The current findings also found this effect in clinical sample.…”
Section: Discussionsupporting
confidence: 83%
“…Empirical findings (Beck, 1986;Beck et al, 1989Beck et al, , 1985 have shown the predictive effects of hopelessness on long-term suicide risk and eventual suicide both in hospitalized depressed patients and outpatients. A recent study in college students with moderate to severe depression symptoms found there was a significant mediating effect of depressive symptom clusters in the relationship between hopelessness and SI (Ballard et al, 2015). However, the mediating effect of depression severity in the relationship between hopelessness and SI has not been examined in clinical sample with MDD.…”
Section: Introductionmentioning
confidence: 96%
“…Previous research also supports the adequacy of scale-level reliability estimates ( r > .80; Ballard, Patel, Ward, & Lamis, 2015; Bryan, Ray-Sannerud, Morrow, & Etienne, 2013). Internal consistency reliability estimates for the current study ranged from .75 to .92 with a total 95% CI [.71, .94].…”
Section: Methodssupporting
confidence: 56%
“…Moreover, the larger effect sizes of mediation of meaning in life variables between the Positive Focus subscale of the FDI-24 and the Suicidal Behaviors Questionnaire-Revised than between the Beck d Hopelessness Scale and the SBQ-R suggested that this subscale is a valuable addition to the measurement of the hopelessness construct. Positive future disposition is not just a reverse of negative future disposition, it has its specific qualitative difference [49], and it does imply a stronger meaning in life and search for meaning, which should be taken into account in screening procedures.…”
Section: Discussionmentioning
confidence: 99%